2007
DOI: 10.1097/mnm.0b013e328013eb1e
|View full text |Cite
|
Sign up to set email alerts
|

Healthy passive cigarette smokers have increased pulmonary alveolar permeability

Abstract: Passive smoking has a functional impact on the lung blood/gas barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 4 publications
2
13
0
1
Order By: Relevance
“…The subjects in the present study were nonsmokers and had a normal BGB permeability in line with other published reference values (Nilsson et al, 1997). In this respect it should be emphasized that the reported effect of daily inhalation of cigarette smoke or environmental tobacco smoke (Beadsmoore et al, 2007;Mason et al, 1983;Jones et al, 1980) is a result of rather intense continuous exposures as compared to the relatively short term exposure to the levels of PM in ambient air in Copenhagen. Indeed, 2 h of ozone exposure at 400 ppb was sufficient to produce significant decrements in pulmonary function and also caused increased BGB permeability measured by 99m Tc-DTPA clearance (Kehrl et al, 1987).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The subjects in the present study were nonsmokers and had a normal BGB permeability in line with other published reference values (Nilsson et al, 1997). In this respect it should be emphasized that the reported effect of daily inhalation of cigarette smoke or environmental tobacco smoke (Beadsmoore et al, 2007;Mason et al, 1983;Jones et al, 1980) is a result of rather intense continuous exposures as compared to the relatively short term exposure to the levels of PM in ambient air in Copenhagen. Indeed, 2 h of ozone exposure at 400 ppb was sufficient to produce significant decrements in pulmonary function and also caused increased BGB permeability measured by 99m Tc-DTPA clearance (Kehrl et al, 1987).…”
Section: Discussionsupporting
confidence: 89%
“…In keeping with tobacco-induced lung injury, it has been shown that smokers have increased BGB permeability (Nolop et al, 1987;Mason et al, 1983;Minty et al, 1981;Jones et al, 1980). A dose-dependent effect can also be inferred from observations that the BGB permeability is higher among smokers than nonsmokers, and passive smokers have BGB permeability in between these extremes (Beadsmoore et al, 2007). Cigarette smoke possibly elicits direct toxicity in alveoli cells with measurable alterations of lung function such as FEV 1 .…”
mentioning
confidence: 95%
“…[23][24][25][26] Public health interventions aimed to limit ETS exposure among adolescents should consider both the home and the out of home environment. Knowledge about who the smoker is, the relationship with the adolescents, where and when smoking occurs, are likely to facilitate planning and delivery of effective ETS prevention programs.…”
Section: Resultsmentioning
confidence: 99%
“…The biological half-life of 99m Tc DTPA is 80 ± 20 min in healthy nonsmokers [10], whereas the biological half-life of 99m TcTechnegas is 135 h [11].…”
Section: Non-diagnosticmentioning
confidence: 99%